Tensões e contradições da participação democrática na América Latina e na Europa - Falanga, Roberto; Ferrão, João (Cadernos Metrópole, 2025)
DOI: https://doi.org/10.1590/2236-9996.2025-6371085-pt https://doi.org/10.1590/2236-9996.2025-6371085-en